Cover Feature: Superior Selectivity and Tolerance towards Metal‐Ion Impurities of a Fe/N/C Catalyst for CO2 Reduction (ChemSusChem 17/2019). Issue 17 (4th September 2019) - Yang, Hui‐Juan; Zhang, Xue; Hong, Yu‐Hao; Sari, Hirbod Maleki Kheimeh; Zhou, Zhi‐You; Sun, Shi‐Gang; Li, Xi‐Fei
Abstract : The Cover Feature shows a promising approach to relieve the pressure of greenhouse effect and provide renewable energy by using the Fe/N/C catalyst for converting CO2 to green energy resources. The low‐cost Fe/N/C catalyst exhibits a high selectivity for the electrocatalytic reduction of CO2 along with an excellent tolerance towards metal‐ion impurities. Thus, improving the possibility of its practical application. More information can be found in the Full Paper by H‐J Yang et al. onpage 3988 in Issue 17, 2019 (DOI:10.1002/cssc.201901330 ).